2014
DOI: 10.1007/s11517-014-1172-8
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission in the chest under surface excitation: an experimental and computational study with diagnostic applications

Abstract: Chest physical examination often includes performing chest percussion, which involves introducing sound stimulus to the chest wall and detecting an audible change. This approach relies on observations that underlying acoustic transmission, coupling, and resonance patterns can be altered by chest structure changes due to pathologies. More accurate detection and quantification of these acoustic alterations may provide further useful diagnostic information. To elucidate the physical processes involved, a realisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Simulations were compared to published results for mice and used in part to calculate a preliminary acoustic damage threshold curve for humans as a function of frequency. Peng et al [17] conducted wide frequency band percussion studies on human and pig chest. Computational models of the upper torso were validated by comparison with experiment measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations were compared to published results for mice and used in part to calculate a preliminary acoustic damage threshold curve for humans as a function of frequency. Peng et al [17] conducted wide frequency band percussion studies on human and pig chest. Computational models of the upper torso were validated by comparison with experiment measurements.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray computed tomography (CT) provides limited contrast for soft biological tissues and also introduces potentially harmful ionizing radiation. Due to these limitations, a preliminary study that utilizes noninvasive measurement of external mechanical wave motion (sound and vibration) for lung injuries was performed in dog and porcine subjects [30, 40]. The study suggested that this method may provide information about lung mechanical property changes, which may have diagnostic value.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Indeed simultaneous, multi-sensor auscultation methods have been developed to "map" sounds on the thoracic surface by several groups. 5,[7][8][9][10][11] Also recently the phase contrast-based technique known as magnetic resonance elastography (MRE) has been applied to the lungs in pilot studies with limited success. [12][13][14][15] MRE seeks to provide a map of the viscoelastic properties within the region of interest that will affect the shear wave motion that MRE measures.…”
Section: Introduction a Motivationmentioning
confidence: 99%